Comparative the effect of bisphenol A and bisphenol S on the development and spectral sensitivity of cone photoreceptors in zebrafish larvae (Danio rerio) - Liguo Qiu; Peng Yu; Qiang Li; Cuiping Wen; Haiyang Wang; Dongying Zhao; Tianyu Zhang; Chenghui Wang; Lixia Liu; Dongxue Li; Shiyong Wen; Yinghui Sun (Ecotoxicology and Environmental Safety)
Color vision, which is mediated by cone photoreceptors in vertebrates, is essential for perceiving the external environment. Bisphenol A (BPA) and its substitute bisphenol S (BPS) have been widely used worldwide, while the evaluation of their safety, especially the newly discovered visual toxicity mechanism caused by them in recent years, has not been clearly explored. In the present study, we investigated the effects of BPA treatment (1, 10, and 100 μg/L) on cone cell development and function to evaluate visual toxicity. We also compared the mechanisms of color deficiency induced by BPA and BPS at the same concentrations. The results indicated that BPA (10 and 100 μg/L) caused the abnormal proliferation (increased number of cone cells), morphological abnormalities (increased height of cone cells), mosaic pattern disorder, and depressed expression of key genes related to the photo-transduction pathway, and impaired the light perception ability of both red and UV cones ultimately. Similar to the BPA exposure group, BPS (1, 10, and 100 μg/L) exposure resulted in structural damage and mosaic arrays disorder of red and UV cone photoreceptors. In contrast to BPA exposure, BPS exposure resulted in significant activation of key genes involved in the phototransduction pathway. Our data indicate that both BPS and BPA exposure can interfere with the development of cone cells, and two types of compounds disturb the transduction of photon signals within cone cells in different ways, which further impaired the retinal spectral sensitivity to the light signal. This study clarifies the root cause for color vision impairment induced by BPA from the perspective of cone-mediated color vision. It also clarified that the BPA and its substitute BPS may not be entirely safe at the single-cell level.